Waldenström Macroglobulinemia diagnosis, risk assessment and treatment in Portugal – results from a Delphi-like Panel - Bergantim, Rui; Chacim, Sérgio; Monteiro, Alexandra; Macedo, Ana M.; Rodrigues, Gonçalo M. C.; da Silva, Maria Gomes (Frontiers in Hematology, 2023)
Clinical features of Waldenström Macroglobulinemia (WM) are variable, often leading to heterogeneous decisions regarding patients' diagnosis, risk stratification, and treatment. This study assessed the agreement rates on WM diagnosis, risk stratification, and active treatment strategies to capture how this heterogeneity may influence national practices among hematologists. A two-round Delphi-like Panel with 22 national hematologists experienced in WM was conducted online, where 33 statements were classified using a 4-point Likert scale. For each statement, the consensus level was set at 70% for "fully agree/disagree"; the majority level was defined as >70% in agreement or disagreement. After two rounds, no statements were categorized as consensus, and 15 out of 33 failed to obtain a qualified majority. Globally, the experts could not reach a qualified majority in approximately half of the sentences from each category (diagnosis, risk assessment, and therapeutic decision), indicating that contradictory opinions are transversal to all the topics involving WM. A lack of consensus in diagnosing and managing WM among Portuguese hematologists became evident. These results illustrate heterogeneity in clinical practices, and future research initiatives should be considered to improve and reinforce accepted guidelines for diagnosing, assessing, and treating WM patients.